Environmental impact of building construction and energy consumption; case study of Iran. Issue 1 (31st December 2022) - Sepehrdoust, Hamid; Javanmard, Davood; Rasuli, Marziyeh
ABSTRACT: The main objective of the present study is to investigate the determinants of environmental impacts, focusing on the impact of construction and energy consumption on the environment in Iran from 1994 to 2019. The results confirmed the existence of a long-term relationship between the variables of construction, energy consumption, and environmental index. The variables of construction and energy consumption had a positive and significant impact on the country's environmental index. The estimated coefficient for the variable of housing investment also showed a positive effect on the environmental index. In general, it is concluded that to reduce the negative impact of construction on the environmental index, it is necessary to change the old construction styles and instead apply new construction strategies in favor of lower energy consumption and less CO2 emissions into the environment.